The Fusion Frontier: How Multi-Modal AI is Revolutionizing Medical Diagnosis with Imaging and Clinical Data - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The complexity of human health often defies simple, single-source analysis. For decades, medical AI has focused on unimodal data—analyzing a chest X-ray for ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine